Risk Factors for Work Fatigue in Welding Workers in the Oil and Gas Industry: Literature Review - Ridho Pradana Mahaputra; Baiduri Widanarko (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Welding workers in the Oil and Gas Industry are often exposed to heat sources such as sunlight and welding machines, especially when working outdoors. The welding process involves cutting, heating, grinding, joining, painting, and sanding, which can lead to significant fatigue, impacting their health and safety. Objective: Workers who do welding are often exposed to heat sources, including sunlight and heat from welding machines because some employees do welding outdoors. Cutting iron, heating, grinding, joining, painting, and sanding are steps in the welding process carried out in a work environment exposed to sunlight. Thus, is fatigue a risk for welding workers in the Oil and Gas Industry. This study aims to determine the level of risk of causing work fatigue in welding workers in the Oil and Gas Industry. Method: This study is a systematic literature review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta Analyses) method. Literature searches were obtained from Google Scholar, Science Direct, and Neliti Jurnal. The keywords "risk of causing work fatigue" and "Risk of Causing Work Fatigue" and "work fatigue in welding workers" and "work fatigue in welding workers" were used in articles published from 2019-2023. with international journal rankings Q1 and Q2. Result: A total of 105 articles were found, but only 16 articles were suitable for use after going through an elimination process that was adjusted to the research topic, passed duplication, and could be accessed in full. There are four risk factors for work fatigue in welding, namely, too much work, lack of time, conflict with welding workers, and the nature of ambiguity in each worker. Conclusion: This finding is useful for knowing the risk factors for work fatigue in welding workers, there are four factors, namely, too much work, lack of time, conflict with welding workers, and the nature of ambiguity in each worker. To reduce the risk at work is by socializing related to occupational safety and health, increasing awareness of the importance of health and safety for workers with the aim of creating safe working conditions and ensuring occupational safety and health.